Osmium tetroxide, 2,2'-bipyridine: electroactive marker for probing accessibility of tryptophan residues in proteins - Fojta, Miroslav; Billová, Sabina; Havran, Ludek; Pivonková, Hana; Cernocká, Hana; Horáková, Petra; Palecek, Emil (Analytical chemistry, 2008)
A complex of osmium tetroxide with 2,2'-bipyridine (Os,bipy) has been applied as a chemical probe of DNA structure as well as an electroactive DNA label. The Os,bipy has been known to form covalent adducts with pyrimidine DNA bases. Besides the pyrimidines, electrochemically active covalent adducts with Os,bipy are formed also by tryptophan (W) residues in peptides and proteins. In this paper we show that Os,bipy-treated proteins possessing W residues (such as avidin, streptavidin, or lysozyme) yield at the pyrolytic graphite electrode (PGE) a specific signal (peak alphaW) the potential of which differs from the potentials of signals produced by free Os,bipy or by Os,bipy-modified DNA. No such signal is observed with proteins lacking W (such as ribonuclease A or alpha-synuclein). Subpicomole amounts of W-containing proteins modified with Os,bipy can easily be detected using adsorptive transfer stripping voltammetry with the PGE. Binding of biotin to avidin interferes with Os,bipy modification of the protein, in agreement with the location of W residues within the biotin-binding site of avidin. These Ws are accessible for modification in the absence of biotin but hidden (protected from modification) in the avidin-biotin complex. The Os,bipy-modified avidin is unable to bind biotin, and its quarternary structure is disrupted. Analogous effects were observed with another biotin-binding protein, streptavidin. Our results demonstrate that modification of proteins with Os,bipy under conditions close to physiological, followed by a simple electrochemical analysis, can be applied in the microanalysis of protein structure and interactions.
Keywords: oxid osmičelý; Cross-Linking Reagents; 2,2'-Dipyridyl; Electrodes; Electrochemistry; tryptofan; biotin; elektrochemie; proteiny; Electrons; 2,2'-dipyridyl; Proteins; avidin; elektrody; Tryptophan; reagencia zkříženě vázaná; molekulární struktura; Avidin; Molecular Structure; Carbon; uhlík; elektrony; Osmium Tetroxide; Biotin